2021
DOI: 10.1177/20427530211032302
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking sociocultural notions of learning in the digital era: Understanding the affordances of networked platforms

Abstract: Understanding the affordances that networked platforms offer is a good place to start rethinking our notions of learning. The article discusses how social connectivity has changed, arguing that networking and networks have become foregrounded in how we perceive and experience our (digital) social worlds. Our aim is to understand the nature of networked structures, and the networked practices that these have enabled, to shed light upon how they ‘work’ for learning. While making use of the concept of affordances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that students were able to identify and actualize the affordances of social media as they perceived that these platforms were flexible and allowed acquiring important information (Ansari & Khan, 2020) from anywhere and at any time (Attard & Holmes, 2020;Greenhow et al, 2019;Stewart, 2015). The functional affordances, for instance usability and practicality, have also been explored in prior studies by Unlüsoy et al (2022) who found that besides editability and replicability which are valuable capacities that allow students to engage with content the social media environment also expanded visibility or exposure to the vast amounts of information.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that students were able to identify and actualize the affordances of social media as they perceived that these platforms were flexible and allowed acquiring important information (Ansari & Khan, 2020) from anywhere and at any time (Attard & Holmes, 2020;Greenhow et al, 2019;Stewart, 2015). The functional affordances, for instance usability and practicality, have also been explored in prior studies by Unlüsoy et al (2022) who found that besides editability and replicability which are valuable capacities that allow students to engage with content the social media environment also expanded visibility or exposure to the vast amounts of information.…”
Section: Discussionmentioning
confidence: 99%
“…Although, educational institutions are increasingly using LMS with social media-like functionalities, it does not support informal learning, educational activities from a socio-constructivist perspective (Van Den Beemt et al, 2020;Garmendía & Cobos, 2013). According to Unlüsoy, Leander, and Haan (2022) social media is an "ever expanding and shrinking collections of nodes and link" that "allow forms of interaction and learning that are fundamentally different" (p. 79) from other learning platforms. Therefore, social media has important implications for rethinking the connectivity or the kinds of social interaction that underlie most of our thinking about learning (Unlüsoy et al, 2022).…”
Section: Social Media Platformsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Bazarova and Choi's (2014) functional model of self-disclosure, people's disclosure goals are influenced by the affordances of SNSs. These affordances can be defined as “the inherent features of a technology, as well as how people interact with and interpret these features” (Unlusoy et al, 2022, p. 80). Examples of affordances are visibility, scalability, and permanence.…”
Section: Literature Reviewmentioning
confidence: 99%